AFAP1‐AS1: A novel oncogenic long non‐coding RNA in human cancers - Zhang, Fuyou (Cell Prolif, 2017)
Long non‐coding RNAs (lncRNAs), a group of non‐protein‐coding RNAs with more than 200 nucleotides in length, are involved in multiple biological processes, such as the proliferation, apoptosis, migration and invasion. Moreover, numerous studies have shown that lncRNAs play important roles as oncogenes or tumour suppressor genes in human cancers. In this paper, we concentrate on actin filament‐associated protein 1‐antisense RNA 1 (AFAP1‐AS1), a well‐known long non‐coding RNA that is overexpressed in various tumour tissues and cell lines, including oesophageal cancer, pancreatic ductal adenocarcinoma, nasopharyngeal carcinoma, lung cancer, hepatocellular carcinoma, ovarian cancer, colorectal cancer, biliary tract cancer and gastric cancer. Moreover, high expression of AFAP1‐AS1 was associated with the clinicopathological features and cancer progression. In this review, we sum up the current studies on the characteristics of AFAP1‐AS1 in the biological function and mechanism of human cancers.